Autocrine T-cell suicide mediated by APO-1/(Fas/CD95) - Dhein, Jens; Walczak, Henning; Bäumler, Caroline Beatrix; Debatin, Klaus-Michael; Krammer, Peter H. (Nature, 1995)
THE APO-l/(Fas/CD95) cell surface receptor is a member of the nerve growth factor (NGF)/tumour necrosis factor (TNF) receptor superfamily and mediates apoptosis1 -4. Peripheral activated T cells (ATC) from lymphoproliferation (Ipr/lpr) mutant mice that express a reduced number of APO-1 receptors have a defect in T-cell receptor (TCR)-induced apoptosis5,6. This suggests that TCR-induced apoptosis involves APO-1. We tested this hypothesis in various human T cells: (1) malignant Jurkat cells, (2) an allo-reactive T-cell clone (S13), and (3) peripheral ATC. TCR triggering through immobilized anti-CD3 antibodies or Staphylococcus enterotoxin B (SEB) superantigen induced expression of the APO-1 ligand and apoptosis in these cells. Anti-CD3-induced apoptosis of Jurkat cells was demonstrated even in single-cell cultures. In all cases apoptosis was substantially inhibited by blocking anti-APO-1 antibody fragments and soluble APO-1 receptor decoys. The APO-1 ligand was found in the supernatant of activated Jurkat cells as a soluble cytokine. We propose that TCR-induced apoptosis in ATC can occur through an APO-1 ligand-mediated autocrine suicide. These results provide a mechanism for suppression of the immune response and for peripheral tolerance by T-cell deletion.